Clinical-pathogenetic and prognostic value of the nitrotyrosine level in the blood serum of patients with coronavirus disease (COVID-19) with pneumonia - Riabokon, O. V.; Kuliesh, I. O.; Bielenichev, I. F.; Riabokon, Yu. Yu.; Рябоконь, Олена Вячеславівна; Кулєш, І. О.; Бєленічев, Ігор Федорович; Рябоконь, Юрій Юрійович (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of the research is to determine the clinical-pathogenetic and prognostic value of nitrotyrosine levels in the blood serum of patients with COVID-19 with pneumonia in the development of oxygen dependence and the risk of fatal outcome. Materials and methods. 123 patients with COVID-19 with pneumonia were examined, who were examined and treated according to the Order of the Ministry of Health of Ukraine dated March 28, 2020 No. 722. Patients were divided into groups: I group – 32 patients with a moderate course without oxygen dependence; II group – 91 patients with a severe course with the presence of oxygen dependence. Patients in the II group were additionally divided into subgroups: II-A subgroup – 45 patients who recovered; II-B subgroup – 46 patients who died. The content of nitrotyrosine (Hycult Biotech, the Netherlands) was determined in the blood serum by the immunoenzymatic method. Statistical data processing was carried out in the program Statistica for Windows 13 (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. The content of nitrotyrosine in the blood serum of patients with COVID-19 with pneumonia in a severe course with the development of oxygen dependence is higher (p < 0.001) than in patients with a moderate course of the disease without signs of oxygen dependence. The level of its increase has an inverse correlation with the oxygen saturation index (r = -0.53, р < 0.05). When hospitalized for 9.0 [7.0; 12.0] day of the disease, under the condition of nitrotyrosine level >481.97 nmol/ml (AUC = 0.909, p < 0.001), the probability of developing oxygen dependence is significant. And under the conditions of nitrotyrosine level >521.96 nmol/ml during this observation period, the probability of a fatal outcome of the disease is significant (AUC = 0.842, p < 0.001). Мета роботи – встановити клініко-патогенетичне та прогностичне значення рівня нітротирозину в сироватці крові у хворих на COVID-19 із пневмонією в розвитку кисневої залежності та ризику летального наслідку. Матеріали і методи. До дослідження залучили 123 хворих на COVID-19 із пневмонією, які обстежені та ліковані згідно з наказом Міністерства охорони здоров’я України від 28.03.2020 р. № 722. Хворих поділили на групи: І – 32 пацієнти з середньотяжким перебігом без кисневої залежності; ІІ – 91 особа з тяжким перебігом і кисневою залежністю. Пацієнтів ІІ групи додатково поділили на підгрупи: ІІ-А – 45 хворих, які одужали; ІІ-В – 46 осіб, які померли. У сироватці крові пацієнтів визначили вміст нітротирозину (Hycult Biotech, Нідерланди) імуноферментним методом. Статистично результати опрацювали в програмі Statistica for Windows 13 (StatSoft Inc., № JPZ804I382130ARCN10-J). Результати. Вміст нітротирозину в сироватці крові хворих на COVID-19 із пневмонією при тяжкому перебігу з розвитком кисневої залежності вищий (р < 0,001), ніж у пацієнтів із середньотяжким перебігом хвороби без ознак кисневої залежності. Рівень його підвищення мав зворотну кореляцію з показником сатурації кисню (r = -0,53, р < 0,05). Під час госпіталізації на 9,0 [7,0; 12,0] день хвороби, якщо рівень нітротирозину становив >481,97 нмоль/мл (AUC = 0,909, p < 0,001), встановлена значуща імовірність виникнення кисневої залежності. Якщо рівень нітротирозину становив >521,96 нмоль/мл у цей період спостереження, то імовірність летального наслідку хвороби значуща (AUC = 0,842, p < 0,001).
Клініко-патогенетичне та прогностичне значення рівня нітротирозину в сироватці крові хворих на коронавірусну хворобу COVID-19 із пневмонією
Riabokon O. V. - ORCID ID: 0000-0002-7394-4649; Kuliesh I. O. - ORCID ID: 0000-0001-5575-9901; Bielenichev I. F. - ORCID ID: 0000-0003-1273-5314; Riabokon Yu. Yu. - ORCID ID: 0000-0002-2273-8511.
Keywords: coronavirus disease; COVID-19; viral infection; pneumonia; oxidative stress; nitrotyrosine; diagnosis; prognosis; коронавірусна хвороба; вірусна інфекція; пневмонія; оксидативний стрес; нітротирозин; діагностика; прогноз